2019
DOI: 10.2147/ott.s210619
|View full text |Cite
|
Sign up to set email alerts
|

<p>TMEFF2 inhibits pancreatic cancer cells proliferation, migration, and invasion by suppressing phosphorylation of the MAPK signaling pathway</p>

Abstract: PurposeThis paper studied the effect of TMEFF2 expression on pancreatic cancer and its mechanism.MethodsA total of 72 pancreatic cancer patients were enrolled. AsPC1 and Panc1 cells were transfected. SB203580 was used to treat AsPC1 cells. CCK8 assay, colony formation analysis, Transwell experiment and Tunel test were performed. In vivo studies in nude mice were conducted. Immunohistochemistry, qRT-PCR and Western blot were used to detect genes expression.ResultsTMEFF2 was downregulated in pancreatic cancer ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 43 publications
(35 reference statements)
0
10
0
Order By: Relevance
“…For example, S100A13 overexpression contributed to tumor metastasis and poor survival in patients with early-stage non-small cell lung cancer [16]. Low TMEFF2 expression was associated with larger tumor size and advanced stage and poor differentiation in pancreatic cancer cells [17]. It was reported that more than 50% of cancer patients have p53 mutations, which may cause cancer therapy resistance, and the underlying mechanism is poorly understood [18].…”
Section: Introductionmentioning
confidence: 99%
“…For example, S100A13 overexpression contributed to tumor metastasis and poor survival in patients with early-stage non-small cell lung cancer [16]. Low TMEFF2 expression was associated with larger tumor size and advanced stage and poor differentiation in pancreatic cancer cells [17]. It was reported that more than 50% of cancer patients have p53 mutations, which may cause cancer therapy resistance, and the underlying mechanism is poorly understood [18].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, AS-tDR-000067 may inhibit the process of apoptosis by targeting PYCARD. As the downstream target genes of AS-tDR-009512, TPM1 [110], TMEFF2 [111], and PTPRJ [112,113] are involved in cell proliferation and metastasis. It has been reported that TPM1 is involved in the inhibition of VSMC proliferation and metastasis [110].…”
Section: Discussionmentioning
confidence: 99%
“…Using RT-PCR, Zhao et al [ 15 ] observed low levels of tomoregulin mRNA in kidney tissue and minimal levels in testis. Han et al [ 48 ] observed the expression of TMEFF2 mRNA and protein in pancreatic cancer and normal pancreatic tissue. Intriguingly, Glynne-Jones et al [ 12 ] used northern tissue arrays and reported TENB2 mRNA present only in prostate tissue and brain (adult and foetal) except in the pituitary gland.…”
Section: Tissue Distributionmentioning
confidence: 99%
“…Yonezawa et al [ 11 ] reported weak expression in stomach fibroblasts, RD human embryonal rhabdomyosarcoma cells and PC12 rat pheochromocytoma cells in addition to the A172 glioblastoma and CHO-K1 cells. Han et al [ 48 ] reported the expression of both the protein and mRNA of TMEFF2 in five pancreatic cancer cell lines—SW1990, Bxpc3, CFPAC1, Panc1 and AsPC1—and in the normal pancreatic ductal epithelial cells HPDE6-C7. Labeur et al [ 6 ] used AtT20 pituitary corticotrope tumour cells for TMEFF2 knockdown studies.…”
Section: Tissue Distributionmentioning
confidence: 99%
See 1 more Smart Citation